Optical forces in photonic Weyl system - Yang Yang; Hsun-Chi Chan; Ke Bi; Gaoyan Duan; Maoxin Liu; Haoyi Wang; Liangsheng Li (New Journal of Physics, 2022)
Topological photonics has attracted extensive attention, since it allows for a platform to explore and exploit versatile nano-optics systems. In particular, the ideal Weyl metamaterials have recently been demonstrated with fascinating phenomena such as chiral zero mode and negative refraction. In this work, we apply the photonic Weyl metamateirals into the optical tweezers. Based on the effective medium approach, the optical force generated by the body state of the Weyl metamaterial is systematically investigated. Interestingly, theoretical results show that for oblique incidence, the optical force spectra present a valley around Weyl frequency with zero magnitude exactly at the Weyl frequency, and the forces show strong optical circular dichroism. In addition, due to the bi-anisotropic properties, transmissions through the Weyl metamaterial exhibit a significant linear-to-circular polarization conversion and the transmitted wavefront acquires spin momenta of photons, which induces abnormal force on chiral particles. Our study may provide potential applications in the optical manipulations, polarization conversions, and wavefront engineering optics.